Playing with History: The Historical Approach to Musical Performance - Butt, John 1960- (Cambridge Cambridge University Press, 2002)
Why do we feel the need to perform music in a historically informed style? Is this need related to wider cultural concerns? In this challenging study, John Butt sums up recent debates on the nature of the early music movement, calling upon a seemingly inexhaustible fund of ideas gleaned from historical musicology, analytic philosophy, literary theory, historiography and theories of modernism and postmodernism. He develops the critical views of both supporters and detractors, claiming ultimately that it has more intellectual and artistic potential than its detractors may have assumed.
Keywords: Historically informed performance